2016
DOI: 10.4240/wjgs.v8.i11.744
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of the literature investigating urogenital function preservation following robotic rectal cancer surgery

Abstract: AIMTo analyses the current literature regarding the urogenital functional outcomes of patients receiving robotic rectal cancer surgery.METHODSA comprehensive literature search of electronic databases was performed in October 2015. The following search terms were applied: “rectal cancer” or “colorectal cancer” and robot* or “da Vinci” and sexual or urolog* or urinary or erect* or ejaculat* or impot* or incontinence. All original studies examining the urological and/or sexual outcomes of male and/or female patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 51 publications
(112 reference statements)
1
15
1
Order By: Relevance
“…They were also concerned about the impact of equipment learning curve on postoperative outcomes because all the procedures were not performed by the same surgical team. Panteleimonitis et al did a critical analysis of currently available evidence of urogenital function following robotic surgery for rectal cancer [ 26 ]. They searched the literature for studies of robotic surgery without conducting a meta-analysis due to great heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…They were also concerned about the impact of equipment learning curve on postoperative outcomes because all the procedures were not performed by the same surgical team. Panteleimonitis et al did a critical analysis of currently available evidence of urogenital function following robotic surgery for rectal cancer [ 26 ]. They searched the literature for studies of robotic surgery without conducting a meta-analysis due to great heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports indicate that robotic surgery is a superior technique for patients with rectal cancer. A recent study found that patients had better urogenital function due to preservation of the pelvic nerves following robotic surgery 4) . Postoperative complications in patients with obesity or lower rectal cancer treated at a single institute were also consistently reduced following robotic surgery 5) .…”
Section: Robotic Surgerymentioning
confidence: 99%
“…With changes in living habits and diet, the incidence of colon cancer in China has increased substantially, and the incidence rate of colon cancer is double the global average ( 2 4 ). Therefore, the effective prevention and treatment of colon cancer has become a focus of medical investigations ( 3 , 5 , 6 ). In addition to traditional surgery, radiotherapy and chemotherapy, the combining of traditional Chinese medicine and Western medicine treatment strategies offer potential in the treatment of the colon cancer ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%